2019
DOI: 10.1177/1941738119883272
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Treatment Protocol in Patellofemoral Pain: Does Treatment Designed According to Subgroups Improve Clinical Outcomes in Patients Unresponsive to Multimodal Treatment?

Abstract: Background: Targeted intervention for subgroups is a promising approach for the management of patellofemoral pain. Hypothesis: Treatment designed according to subgroups will improve clinical outcomes in patients unresponsive to multimodal treatment. Study Design: Prospective crossover intervention. Level of Evidence: Level 3. Methods: Patients with patellofemoral pain (PFP; n = 61; mean age, 27 ± 9 years) were enrolled. Patients with PFP received standard multimodal treatment 3 times a week for 6 weeks. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
0
11
0
2
Order By: Relevance
“…Recent research in PFP shows that risk factors are not only multifactorial but that some combinations tend to occur together, forming different subgroups [ 2 , 3 ]. Rehabilitating subjects in accordance with the main risk factors [ 4 ] and subgroups considerably improves the outcomes [ 5 ]. These results show that knowledge about the main risk factors in one sport or group of patients plays a key role in developing successful rehabilitation and prevention programs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research in PFP shows that risk factors are not only multifactorial but that some combinations tend to occur together, forming different subgroups [ 2 , 3 ]. Rehabilitating subjects in accordance with the main risk factors [ 4 ] and subgroups considerably improves the outcomes [ 5 ]. These results show that knowledge about the main risk factors in one sport or group of patients plays a key role in developing successful rehabilitation and prevention programs.…”
Section: Introductionmentioning
confidence: 99%
“…Of the three studies undertaken in newly diagnosed PFP patients, two were undertaken in the United Kingdom (UK): London [28] and the UK wide TIPPs (Targeted Interventions for Patellofemoral Pain study) [15], and one in Turkey [29]. All three studies used the same participant eligibility criteria used in previous studies [30,31].…”
Section: Description Of Datasetsmentioning
confidence: 99%
“…In total 85 participants were recruited between May 2015 and May 2017, of whom 81 had patella Tsk measurements. Methods are reported in Yosmaoğlu et al [29]. In addition, to temperature, the PFP datasets included information on age, sex, bilateral pain, ambient room temperature, patella Tsk and tibialis anterior muscle Tsk.…”
Section: Description Of Datasetsmentioning
confidence: 99%
“…It is believed that the main reason for this uncertainty is in strengthening both hip and knee muscle groups in the same exercise program. 11 , 19 , 20 As a result, difficulties are arising in determining the actual effects of isolated hip or knee muscle strengthening on PFP. A review concerning the rehabilitation of patients with PFP focusing on resistance exercise of hip versus knee muscles concluded that hip muscle strengthening is effective in reducing pain and improving function.…”
Section: Introductionmentioning
confidence: 99%